2019
DOI: 10.1109/jsac.2019.2929381
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Optical Spatial Modulation for Mobile Users: Toward a Practical Design for LiFi Systems

Abstract: Among the challenges of realizing the full potential of light-fidelity (LiFi) cellular networks are user mobility, random device orientation and blockage. In the paper, we study the impact of those challenges on the performance of LiFi networks in an indoor environment using measurement-based channel models, unlike existing studies that rely on theoretical channel models. In our work, we adopt spatial modulation (SM), which has been shown to be energy efficient in many applications, including LiFi. We consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…When the communication link is interrupted by blockers, adding extra power cannot compensate for the data loss. Solutions to simplify the effect of link blockage were introduced in [136], [153], [154]. A multi-directional receiver (MDR) for which PDs are located at different sides of a smartphone is introduced in [136], [153] and has been assessed in the presence of link blockage, user mobility as well as device random orientation.…”
Section: Incorporating Realistic and Measurements Based Vlc Channementioning
confidence: 99%
See 1 more Smart Citation
“…When the communication link is interrupted by blockers, adding extra power cannot compensate for the data loss. Solutions to simplify the effect of link blockage were introduced in [136], [153], [154]. A multi-directional receiver (MDR) for which PDs are located at different sides of a smartphone is introduced in [136], [153] and has been assessed in the presence of link blockage, user mobility as well as device random orientation.…”
Section: Incorporating Realistic and Measurements Based Vlc Channementioning
confidence: 99%
“…Solutions to simplify the effect of link blockage were introduced in [136], [153], [154]. A multi-directional receiver (MDR) for which PDs are located at different sides of a smartphone is introduced in [136], [153] and has been assessed in the presence of link blockage, user mobility as well as device random orientation. It is denoted that the MDR structure outperforms the conventional configuration for which all PDs are placed on one side of a smartphones, for example on the screen side.…”
Section: Incorporating Realistic and Measurements Based Vlc Channementioning
confidence: 99%
“…This topic is only explored to a small extent in literature. The authors in [13] analyze the impact of blockage on the bit error rate and the signal-to-noise ratio. The work in [14] investigates the effect of blockage on the outage probability considering different blockage densities.…”
Section: Related Workmentioning
confidence: 99%
“…It is shown that the polar angle can be modeled by either the Laplace distribution (for static users) or the Gaussian distribution (for mobile users) while the azimuth angle follows a uniform distribution. Solutions to alleviate the impact of device random orientation on received SNR and throughput are proposed in [20]- [22]. In [20], the statistics of Euler rotation angles are provided based on the experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Solutions to alleviate the impact of device random orientation on received SNR and throughput are proposed in [20]- [22]. In [20], the statistics of Euler rotation angles are provided based on the experimental measurements. Then, simulations of BER performance for spatial modulation using a multi-directional receiver configuration with consideration of random device orientation is evaluated.…”
Section: Introductionmentioning
confidence: 99%